A modeling and performance of the triple field plate HEMT - Kourdi Zakarya; Abdelkhader Hamdoun (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
We present this work by two steps. In the first one, the new structure proposed of the FP-HEMTs device (Field plate High Electron Mobility Transistor) with a T-gate on an 4H-SIC substrate to optimize these electrical performances, multiple field-plates were used with aluminum oxide to split the single electric field peak into several smaller peaks, and as passivation works to reduce scaling leakage current. In the next, we include a modeling of a simulation in the Tcad-Silvaco Software for realizing the study of the influence of negative voltage applied to gate T-shaped in OFF state time and high power with ambient temperature, the performance differences between the 3FP and the SFP devices are discussed in detail.